Risk Factors and Triggers of Venous Thromboembolism in Patients with Myocardial Infarction - Sejrup, Joakim Knutsen (UiT The Arctic University of Norway, 2022)
During the past decades, extensive data from the general population have revealed that patients with acute myocardial infarction (MI) are at increased risk of venous thromboembolism (VTE, i.e., deep vein thrombosis [DVT] and pulmonary embolism [PE]). The risk is highest in the initial 0-6 months following an acute MI, and declines rapidly thereafter. The explanation for the observed association between MI and future risk of incident VTE is yet unknown. The overall aim of the present thesis was to identify triggers and risk factors of VTE in patients with MI that potentially can be used to identify MI patients with high risk of VTE. In Paper I, we used a case-crossover designed study with the incident VTE cases recruited from the fourth survey of the Tromsø Study. A case-crossover design is well-suited for studying transient risk factors or triggers on the risk of acute events. The study populations for Paper II and Paper III were recruited from the fourth, fifth and sixth surveys of the Tromsø Study. In Paper II, the participants consisted of a subgroup with extended genetic information. Study subjects in Paper II and Paper III were followed from the first survey they attended to the date of an incident VTE, the date of death or migration, or until administrative censoring at the end of follow-up. First, we found that an MI is a strong trigger factor for VTE, and that indirect risk factors related to the MI, in particular acute infections and immobilization, may to a large extent explain the observed association between MI and VTE. Second, we showed that five prothrombotic genotypes did not explain the increased risk of VTE in MI patients, implying that the prothrombotic genotypes may not play a crucial role in the development of VTE after MI. Third, we demonstrated that the combined effect of MI and obesity on overall VTE risk exceeded the sum of the separate effects. In non-obese subjects, MI was not associated with DVT and unprovoked VTE. Thus, the increased risk of these subtypes of outcomes in MI patients ...